Construcción sostenible: Implementación de la metodología de certificación LEED para la evaluación de la sostenibilidad en proyectos constructivos (2017)
The construction sector is one of the most critical sources of negative environmental impact. For this reason, researchers in the world have taken on the challenge of changing and redefining the different construction processes, taking into account the conservation of natural resources, the reuse of materials, recycling of materials, environmental protection, the non-use of toxic materials, economic benefits, and the quality of the various processes during the construction project. In Colombia there are already many sustainable construction projects, however, in the city of Tunja, there is a deficit of these projects, especially in the construction of sustainable housing. Thus, this project aims to implement the concept of sustainable construction through the application of LEED certification. A middle socioeconomic stratum house in the city of Tunja was selected as a case study. The results show that the construction project in the traditional context obtained a LEED rating of 24 points. However, through the implementation of sustainable strategies, a score of 74 points or “Gold Certification” was achieved. With the obtained results, it can be concluded that, through the implementation of sustainable strategies, in the different construction processes such as the selection of the construction site, the sustainable management of water and energy, the sustainable use of materials and the implementation of sustainable technologies, the construction sector can reduce its negative environmental impact.